Peranan Pendidikan Karakter dan Pembinaan Iman Terhadap Kerohanian Peserta Didik SDTK Dan SMPTK PNIEL Sumba Barat Daya Nusa Tenggara Timur Berdasarkan Kitab Kolose 3 : 12-14 - Marthen Bulu Dairo (Syntax Idea)
Character is the temperament, nature, morals, or personality that distinguishes one individual from another. It can also be described as the true state within a person that sets them apart from others. The purpose of this research is to identify the factors causing school dropout among children in Jangrana village, Kesugihan sub-district, Cilacap Regency. The focus is on children who drop out of primary education due to family environmental factors, particularly the burden placed on parents due to the large number of dependents. The methodology employed in this research is a qualitative approach, combining library research with field studies. It aims to explain the importance of character education and the cultivation of faith among students in SDTK (elementary school) and SMPTK (junior high school) based on the scripture from Colossians 3:12-14. The study is conducted at SDTK and SMPTK schools in Pniel village, Lolo Murri village, Raba Ege sub-district, West Wewewa, Southwest Sumba Regency, East Nusa Tenggara. The observation was carried out by the author, as he/she pioneered these schools. The research findings indicate that the chosen people of God, sanctified and loved by Him, should put on compassion, kindness, humility, gentleness, and patience. They should bear with one another and forgive each other, just as the Lord forgave them. Therefore, they should act accordingly.